2018
DOI: 10.3389/fonc.2018.00514
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytotoxic Activity of Mitochondrial Mechanical Effectors in Human Lung Carcinoma H520 Cells: Pharmaceutical Implications for Cancer Therapy

Abstract: Cancer cell mitochondria represent an attractive target for oncological treatment as they have unique hallmarks that differ from their healthy counterparts, as the presence of a stronger membrane potential that can be exploited to specifically accumulate cytotoxic cationic molecules. Here, we explore the selective cytotoxic effect of 10-N-nonyl acridine orange (NAO) on human lung carcinoma H520 cells and compare them with healthy human lung primary fibroblasts. NAO is a lipophilic and positively charged molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Once inside the cell, Ir III complexes have been shown to specifically target different organelles. For example, cyclometallated Ir III effective photodynamic therapy agents reported by Lim, Rhee, and Kwon and by Brabec and Ruiz, have been found to allocate in the cell endoplasmic reticulum . Fluorophore‐tagged iridium‐hydride complexes have been reported by Liu and Zhao to be internalized in the mitochondria, and preferential targeting of the cancer cell lysosomes by Cp x ‐iridium complexes has been recently reported by Liu …”
Section: Introductionmentioning
confidence: 92%
“…Once inside the cell, Ir III complexes have been shown to specifically target different organelles. For example, cyclometallated Ir III effective photodynamic therapy agents reported by Lim, Rhee, and Kwon and by Brabec and Ruiz, have been found to allocate in the cell endoplasmic reticulum . Fluorophore‐tagged iridium‐hydride complexes have been reported by Liu and Zhao to be internalized in the mitochondria, and preferential targeting of the cancer cell lysosomes by Cp x ‐iridium complexes has been recently reported by Liu …”
Section: Introductionmentioning
confidence: 92%
“…28 Moreover, anticancer complexes with strong lipophilic properties may disrupt normal metabolic homeostasis and intracellular ROS levels by increased binding to mitochondrial membranes. [29][30][31] Notably, the coordination mode of the above-mentioned cyclometalated N,N-chelating iridium(III) complexes was sp 2 -N/ sp 2 -N imine-metal (CvN → metal, Scheme 1, II-V). In contrast, the reported cyclometalated diamine-based iridium(III) complexes chelating sp 3 -N/sp 3 -N donor ligands (H 2 N → metal, Scheme 1, VI) were found to be localized in the lysosomal compartments.…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrion membrane potential of cancer cells is higher (60 mV) than those of normal cells; therefore, the lipophilic cations are more likely to be enriched in mitochondria of cancer cells. In addition, drugs with strong lipophilic properties can increase the affinity for mitochondrial membranes, which can disrupt the normal metabolic homeostasis of mitochondria and lead to dysregulation of intracellular levels of reactive oxygen species (ROS). , Yi et al reported a highly positive Ir III bipyridine complex with high cellular uptake efficiency and satisfactory performance in mitochondrial localization imaging, which significantly inhibits the growth of HepG2 cells . A series of imidazole-substituted Ir III complexes with lipophilicity could aggregate in water and target mitochondria, further resulting in a decrease in the MMP (mitochondrial membrane potential) and the destruction of mitochondrial integrity .…”
Section: Introductionmentioning
confidence: 99%